DETERMINING MACROECONOMIC FACTOR OF FINANCIAL DISTRESS IN MALAYSIA - Sairin, Nur Hidayati; Salisi, Mohd Shamlie; Bujang, Imbarine (Malaysian Journal of Business and Economics (MJBE), 2020)
The companies that have financial distress will become a dangerous threat to many of economic agents such as the investor, managers, client, employee and bankers that hold an interest in the companies. The financial failure or distress of the company not only effect many parties but also towards the company itself, as it need a large amount of cost to be used to stabilize the condition of the company. Due to that, there are several researchers that suggest the macroeconomic indicators do have a significant impact towards the financial distress. However, the macroeconomic factors are rarely used in a study as a variable in predicting the financial distress of a company because of some researchers suggest that the macroeconomic variables have already been considered for the financial ratio variables. Therefore, the purpose of this study is to investigate the significant macroeconomic indicators on financial distress company in Malaysia by determining the relationship between each of the macroeconomic variables towards the financial distress company. This study will use a sample of a company from Bursa Malaysia which is from Practice Note 17 (PN17) with 10 years of periods of time. Thus, the result shows that the real interest rate (RIR), consumer price index (CPI), producer price index (PPI) and money supply (M2) have a significant effect on financial distress companies. While, for the non-financial distress, the macroeconomic indicators that have significant effect on the non-financial distress companies are the gross domestic product (GDP), consumer price index (CPI), producer price index (PPI) and money supply (M2). Therefore, the macroeconomic factor does have a high explanatory on the financial distress in Malaysia.